Diseminasi Mesin Penyuir Daging bagi UMKM “Mahkota Abon” Dusun Ngebo, Ngaglik, Sleman - Sutrisna Sutrisna; Didit Setyo Pamuji; Syah Putra Anggara; Rizky Aji Setiawan (Retii, 2022)
Shredded is a food that is quite popular in the community because of its soft taste and texture and has a long shelf life, so it is very suitable to be used as processed meat products to make it more durable. Making Beef Shredded consists of several stages ranging from boiling, refining fibers or shredding meat, mixing spices, soaking, frying, and draining oil. Mahkota Abon Business Group is a Abon business group located on Jl. Kaliurang Dusun Ngebo Rt. 07, Rw. 23, Sukoharjo, Ngaglik, Sleman, Yogyakarta, which in the process of making the shredded meat is still simple and manual, especially in the roasting process which requires a lot of energy and time. Meat shredding machine has been made and effectively can be operated easily to produce hygienic meat slices. Therefore, through this service, it is hoped that the shredded production capacity of MSME partners will increase both in terms of quantity and quality. The socio-economic impact after this service is carried out is an increase in knowledge about the components, workings, and maintenance of the meat frying machine, so it is hoped that the shredded meat produced by partners will increase in quality and quantity.